Resin-based hard carbon material, method for preparing the same, and sodium-ion battery
Patent Information
- Application Number
- CN202510525009.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
但是常规使用管式炉合成C-COPNA树脂的过程中出现以下问题:(1)管式炉恒温区域有限,只适用于实验室小型试验;(2)固化过程会有水蒸气、低碳烃类等气体释放
[0023]通过上述技术方案,本公开提供一种树脂基硬碳材料及其制备方法和钠离子电池,该方法的预交联在低于300℃的低温下进行,且固化在运动状态下进行,能够使材料受热更加均匀,避免局部热点以及固化过程中产生的气体无法释放、产物呈泡沫状等问题,得到高含量、均匀的第二树脂产物;对第二树脂产物进行氧化处理,得到高氧含量的氧化沥青,由于氧杂原子的存在,沥青在热解碳化过程中不易形成有序的结构,从而得到层间距适宜、无序度高的硬碳材料。将该硬碳材料作为钠离子电池的负极材料时,能够有效提高电池的首次放电比容量和可逆容量。
Smart Images

Figure CN122977348A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of materials, specifically to a resin-based hard carbon material, a method for preparing the same, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries, as a potential alternative to lithium-ion batteries, have broad application prospects. However, sodium ion storage requires suitable anode materials. Traditional graphite materials cannot be directly used in sodium batteries, thus necessitating the search for suitable anode materials. Asphalt, as a carbon precursor, possesses advantages such as high carbon content and abundant resources; however, its tendency to form ordered structures during high-temperature carbonization is detrimental to sodium ion storage. Existing asphalt preparation methods are typically low-cost and simple to operate, but the resulting material surface has fewer pores and smaller interlayer spacing, hindering rapid sodium ion insertion / extraction.
[0003] To prepare hard carbon materials suitable for sodium ions, pretreated asphalt needs to be cross-linked to synthesize COPNA resin, giving it a certain porous structure to provide more adsorption sites and transport channels for sodium ions. COPNA resin, or condensed polycyclic aromatic hydrocarbon resin, is a thermosetting resin with a three-dimensional structure. It is divided into three stages according to the degree of polymerization: A-COPNA resin refers to a resin with a low degree of polymerization, which is a liquid that can flow at room temperature; B-COPNA resin refers to a resin with a certain degree of polymerization, which is solid at room temperature, can melt when heated, and is soluble in most organic solvents; C-COPNA resin refers to a resin with a three-dimensional network structure that is insoluble in organic solvents and does not melt when heated, and is an excellent precursor for hard carbon materials. However, the following problems occur in the conventional process of synthesizing C-COPNA resin using a tube furnace: (1) The constant temperature area of the tube furnace is limited, and it is only suitable for small-scale laboratory experiments; (2) Water vapor, low-carbon hydrocarbons, and other gases are released during the curing process.
[0004] CN111244407A discloses a method for preparing a hard carbon / graphite composite anode material for lithium-ion batteries, comprising the following steps: S1: cross-linking a hard carbon source to obtain a hard carbon precursor, wherein the hard carbon source is a thermoplastic polymer or a non-thermoplastic polymer; S2: liquid-phase mixing of graphite, the hard carbon precursor, and additives followed by drying; S3: pre-carbonization treatment and carbonization treatment; S4: surface coating treatment. This method is complex and difficult to implement for large-scale production or has high production costs.
[0005] CN117466279A discloses a method for preparing a COPNA resin-based sodium-carbon ion battery anode material, including a high-temperature carbonization step: heating COPNA resin to 600℃~1600℃ under an inert atmosphere, holding at that temperature for 0.5~3 hours, and then naturally cooling to room temperature before removal. The hard carbon material prepared by this method has low reversible capacity. Summary of the Invention
[0006] The purpose of this disclosure is to provide a resin-based hard carbon material, its preparation method, and a sodium-ion battery. The method involves curing under dynamic conditions, which can synthesize a second resin product with a high content and uniform distribution of a three-dimensional network structure. After oxidation treatment and high-temperature carbonization, a resin-based hard carbon material with a suitable sodium storage content is obtained. This hard carbon material exhibits excellent electrochemical performance when used as a negative electrode material for sodium-ion batteries.
[0007] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing resin-based hard carbon materials, the method comprising:
[0008] (1) Pre-crosslinking is performed by contacting asphalt with a crosslinking agent, wherein the pre-crosslinking temperature is below 300°C, to obtain a first resin product;
[0009] (2) The first resin product is crushed to make the resulting resin particles move and then solidified to obtain the second resin product.
[0010] (3) Oxidize and carbonize the second resin product.
[0011] Optionally, in step (1), the ash content in the asphalt is less than 0.01% by mass and the metal content is less than 10 μg / g.
[0012] Optionally, the asphalt includes one or more of natural asphalt, coal-based asphalt, and petroleum-based asphalt, wherein the coal-based asphalt includes coal tar pitch and / or direct coal liquefaction pitch, and the petroleum-based asphalt includes vacuum residue pitch and / or heavy aromatic hydrocarbon pitch.
[0013] The crosslinking agent comprises an oxygen-containing organic compound having one or more of hydroxyl, carboxyl, and aldehyde groups; preferably, the oxygen-containing organic compound contains a benzene ring; more preferably, the oxygen-containing organic compound comprises a phenolic compound having 6 to 20 carbon atoms and 1 to 3 phenolic hydroxyl groups.
[0014] Optionally, in step (1), the weight ratio of the asphalt to the crosslinking agent is (0.5-4):1, preferably (1-2):1;
[0015] The pre-crosslinking temperature is 150–250°C, preferably 200–250°C; the heating rate is 1–10°C / min; and the holding time is 10–60 min.
[0016] Optionally, in step (2), the way to achieve the motion state includes placing the resin particles in a rotary heating furnace for rotation, wherein the rotation speed of the rotary heating furnace is 1 to 30 r / min;
[0017] The curing temperature is 250–450℃, preferably 320–450℃; the heating rate is 1–10℃ / min; and the holding time is 1–5h.
[0018] Optionally, in step (2), the pulverization conditions include: pulverizing the first resin product using a pulverizer until the particle size D10 is <1μm, D50 is <5μm, and D90 is <10μm, to obtain resin particles, and then curing the resin particles.
[0019] Optionally, in step (3), the oxidation conditions include: in an air or oxygen atmosphere, the second resin product is heated to 200-400°C, preferably 320-400°C, at a heating rate of 1-10°C / min for oxidation, and the oxidation isothermal time is 2-6 hours.
[0020] Optionally, in step (3), the carbonization conditions include: in an inert gas atmosphere, heating the oxidized product to 1100-1600℃, preferably 1300-1600℃, at a heating rate of 1-10℃ / min for carbonization, and the carbonization isothermal time is 2-8h; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.
[0021] The second aspect of this disclosure provides a resin-based hard carbon material prepared using the method described in the first aspect of this disclosure.
[0022] This disclosure provides a sodium-ion battery, the sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the resin-based hard carbon material described in the second aspect of this disclosure.
[0023] Through the above technical solution, this disclosure provides a resin-based hard carbon material, its preparation method, and a sodium-ion battery. The pre-crosslinking of this method is carried out at a low temperature below 300°C, and the curing is performed in motion, which enables more uniform heating of the material and avoids problems such as local hot spots, the inability to release gases generated during curing, and foamy products, resulting in a high-content, uniform second resin product. The second resin product is then oxidized to obtain oxidized asphalt with a high oxygen content. Due to the presence of oxygen heteroatoms, the asphalt is less likely to form an ordered structure during pyrolysis and carbonization, thus obtaining a hard carbon material with suitable interlayer spacing and high disorder. When this hard carbon material is used as the negative electrode material of a sodium-ion battery, it can effectively improve the battery's initial discharge specific capacity and reversible capacity.
[0024] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description
[0025] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:
[0026] Figure 1 This is a charge-discharge curve of a battery assembled from the hard carbon material prepared in Example 1 of this disclosure at a current density of 0.1C.
[0027] Figure 2 This is a SEM image of the hard carbon material prepared in Example 1 of this disclosure;
[0028] Figure 3 This is a TEM image of the hard carbon material prepared in Example 1 of this disclosure;
[0029] Figure 4 This is the XRD pattern of the hard carbon material prepared in Example 1 of this disclosure;
[0030] Figure 5 This is a particle size distribution diagram of the hard carbon material prepared in Example 1 of this disclosure. Detailed Implementation
[0031] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.
[0032] The first aspect of this disclosure provides a method for preparing a resin-based hard carbon material, the method comprising:
[0033] (1) Pre-crosslinking is performed by contacting asphalt with a crosslinking agent, wherein the pre-crosslinking temperature is below 300°C, to obtain a first resin product;
[0034] (2) The first resin product is crushed to make the resulting resin particles move and then solidified to obtain the second resin product.
[0035] (3) Oxidize and carbonize the second resin product.
[0036] The pre-crosslinking of the method provided in this disclosure is carried out at a low temperature below 300°C, and the curing is carried out in motion, which can make the material heat more uniformly and avoid problems such as local hot spots, inability to release gas generated during curing, and foamy products, resulting in a high-content and uniform second resin product. The second resin product is oxidized to obtain oxidized asphalt with high oxygen content. Due to the presence of oxygen heteroatoms, the asphalt is not easy to form an ordered structure during pyrolysis and carbonization, thus obtaining a hard carbon material with suitable interlayer spacing and high disorder.
[0037] In this disclosure, the first resin product is B-COPNA resin and the second resin product is C-COPNA resin, which are excellent precursors for hard carbon materials.
[0038] In an optional embodiment, step (1) further includes: contacting asphalt, petroleum-based heavy oil with a crosslinking agent to perform the pre-crosslinking, wherein the petroleum-based heavy oil includes one or more of catalytic slurry, ethylene tar and styrene tar.
[0039] In one embodiment of this disclosure, in step (1), the ash content in the asphalt is less than 0.01% by mass, and the metal content is less than 10 μg / g. In a specific embodiment, the asphalt can be pretreated before the pre-crosslinking in step (1) to obtain asphalt with the above-mentioned parameter range. In the above embodiments, selecting the preferred asphalt is beneficial for improving the electrochemical performance of hard carbon materials.
[0040] In one embodiment of this disclosure, the asphalt includes one or more of natural asphalt, coal-based asphalt, and petroleum-based asphalt. The coal-based asphalt includes coal tar pitch and / or direct coal liquefaction pitch, and the petroleum-based asphalt includes vacuum residue pitch and / or heavy aromatic hydrocarbon pitch. In a preferred embodiment, the asphalt is coal-based asphalt.
[0041] In one embodiment, the crosslinking agent comprises an oxygen-containing organic compound having one or more of hydroxyl, carboxyl, and aldehyde groups; preferably, the oxygen-containing organic compound contains a benzene ring; more preferably, the oxygen-containing organic compound comprises a phenolic compound having 6 to 20 carbon atoms and 1 to 3 phenolic hydroxyl groups, for example, the oxygen-containing organic compound may be hydroquinone. In the above embodiments, by selecting a preferred crosslinking agent, it is beneficial for the crosslinking agent and asphalt to undergo a co-crosslinking reaction, forming a short-range ordered and long-range disordered structure.
[0042] In one embodiment of this disclosure, in step (1), the weight ratio of the asphalt to the crosslinking agent is (0.5-4):1, preferably (1-2):1.
[0043] In one embodiment, the pre-crosslinking temperature is 150–250°C, preferably 200–250°C; the heating rate is 1–10°C / min; and the holding time is 10–60 min.
[0044] In one embodiment of this disclosure, step (2) involves rotating the resin particles in a rotary kiln at a speed of 1–30 r / min. The motion state described in this disclosure is a non-static state, and the method of achieving the motion state is not limited. For example, the resin particles can also be placed in a boiling kiln or a stirred tank to maintain the motion state.
[0045] In one embodiment, the curing temperature is 250–450°C, preferably 320–450°C; the heating rate is 1–10°C / min; and the holding time is 1–5 h.
[0046] In one embodiment of this disclosure, step (2) includes the following pulverization conditions: pulverizing the first resin product using a pulverizer until the particle size (D10) is <1 μm, the particle size (D50) is <5 μm, and the particle size (D90) is <10 μm, to obtain resin particles, which are then cured. The pulverizer includes an air jet mill or a ball mill, but other types of pulverizers are also acceptable. In the above embodiment, the preferred pulverizer is selected to ensure more uniform heating of the material during curing and to effectively release the gas generated during curing, preventing the product from becoming foamy.
[0047] Since the curing process of this disclosure is carried out at high temperature, some oxygen heteroatoms in the material will be removed. Therefore, the second resin product obtained after curing needs to be oxidized to obtain oxidized asphalt with a certain oxygen content. In one embodiment, the oxidation conditions in step (3) include: oxidizing the second resin product at a heating rate of 1 to 10 °C / min to 200 to 400 °C, preferably 320 to 400 °C, in an air or oxygen atmosphere, and maintaining the oxidation temperature for 2 to 6 hours.
[0048] In one embodiment of this disclosure, in step (3), the carbonization conditions include: in an inert gas atmosphere, heating the oxidized product to 1100-1600°C, preferably 1300-1600°C, at a heating rate of 1-10°C / min for carbonization, and the carbonization isothermal time is 2-8 hours; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.
[0049] The second aspect of this disclosure provides a resin-based hard carbon material prepared using the method described in the first aspect of this disclosure.
[0050] This disclosure provides a sodium-ion battery, the sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the resin-based hard carbon material described in the second aspect of this disclosure.
[0051] The present disclosure is further illustrated by the following examples, but the disclosure is not limited thereto. Unless otherwise specified, all raw materials used in the following examples are commercially available products. The coal direct liquefaction pitch is manufactured in-house by the Research Institute of Petroleum Processing and Chemical Industry.
[0052] The morphological characteristics of hard carbon materials were analyzed using scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM). The instruments were Hitachi S4800 and JEM-2100 (Japan Electronics Corporation), respectively.
[0053] The disorder and interlayer spacing of hard carbon materials were analyzed by X-ray diffraction (XRD) using a Shimadzu XRD-6000 X-ray diffractometer from Japan.
[0054] The particle size of hard carbon materials was analyzed using a Mastersizer 3000 optical particle size analyzer.
[0055] The electrochemical performance of hard carbon materials was tested using a Blue Electricity testing system, instrument model CT3001A.
[0056] Example 1
[0057] (1) Mix 50g of pretreated coal direct liquefaction pitch with 50g of hydroquinone (crosslinking agent), and heat to 200℃ at a heating rate of 5℃ / min for pre-crosslinking. The temperature is held for 15min to obtain B-COPNA resin. The weight ratio of pitch to crosslinking agent is 1:1. The properties of the pretreated coal direct liquefaction pitch are shown in Table 1.
[0058] (2) B-COPNA resin was pulverized using an air jet mill until the particle size D10 was <1μm, D50 was <5μm, and D90 was <10μm, resulting in B-COPNA resin particles. The B-COPNA resin particles were then placed in a rotary kiln and rotated at a speed of 3r / min. The temperature was then increased to 350℃ at a rate of 2℃ / min for curing. The curing time was 4h, resulting in C-COPNA resin particles.
[0059] (3) The C-COPNA resin particles were oxidized in air at a heating rate of 2℃ / min to 320℃ and the oxidation was constant for 3h to obtain the oxidized product; the oxidized product was carbonized in nitrogen atmosphere at a heating rate of 5℃ / min to 1500℃ and the carbonization was constant for 2h to obtain COPNA resin-based hard carbon material.
[0060] SEM image of the COPNA resin-based hard carbon material is shown below. Figure 2 TEM image Figure 3 XRD pattern as follows Figure 4 As shown, the particle size distribution diagram is as follows: Figure 5 As shown.
[0061] Figure 2 The hard carbon material prepared in Example 1 shows that it has a small particle size and a large specific surface area.
[0062] Figure 3 The hard carbon material prepared in Example 1 exhibits a graphite sheet structure characterized by short-range order and long-range disorder.
[0063] Figure 4 The XRD pattern shows that the hard carbon material prepared in Example 1 exhibits a disordered structure, and a characteristic diffraction peak appears at 2θ = 23.189°. This characteristic diffraction peak indicates that the interlayer spacing d of the hard carbon material is... 002 The interlayer spacing is 0.383 nm, which is conducive to the rapid insertion and extraction of sodium ions.
[0064] Figure 5 The particle size distribution of this hard carbon material ranges from 1 to 10 μm.
[0065] Example 2
[0066] Similar to Example 1, the only difference is that the pretreated coal direct liquefaction pitch in step (1) is 60g, so that the weight ratio of the pretreated coal direct liquefaction pitch to the crosslinking agent is 1.2:1.
[0067] Example 3
[0068] Same as Example 1, except that the pre-crosslinking temperature in step (1) is 180°C and the holding time is 10 min.
[0069] Example 4
[0070] Same as Example 1, except that the curing temperature in step (2) is 300°C.
[0071] Example 5
[0072] Same as Example 1, except that the oxidation temperature in step (3) is 300°C and the holding time is 1 hour.
[0073] Example 6
[0074] Same as Example 1, except that the carbonization temperature in step (3) is 1200°C.
[0075] Comparative Example 1
[0076] Same as in Example 1, except that in step (2), B-COPNA resin is placed in a tube furnace and cured in a static state.
[0077] Comparative Example 2
[0078] Same as Example 1, except that step (2) is omitted, and the B-COPNA resin obtained in step (1) is directly oxidized and carbonized in step (3).
[0079] Comparative Example 3
[0080] Same as in Example 1, except that: in step (2), the material is not pulverized before curing, so that the D10 particle size of the cured B-COPNA resin is >1μm, the D50 particle size is >5μm, and the D90 particle size is >10μm.
[0081] Comparative Example 4
[0082] Same as Example 1, except that the pre-crosslinking temperature in step (1) is 300°C.
[0083] Table 1 Properties of pretreated coal direct liquefaction pitch
[0084] project data <![CDATA[Density, g / cm 3 > 1.10 S content, % 0.10 N content, % 0.68 O content, % 5.20 Machine miscellaneous, % <0.03 Ash content, % <0.01 Metal content, μg / g <10.0
[0085] Test case
[0086] The hard carbon materials prepared in the examples and comparative examples were mixed with conductive carbon black and a binder to form a slurry, which was then uniformly coated onto aluminum foil and dried to form an electrode. A sodium metal sheet was used as the counter electrode, a glass fiber membrane was used as the separator, 1 mol NaClO4 was used as the electrolyte, and DMC and EC (volume ratio 1:1) were used as the electrolyte solution to prepare a coin-type sodium-ion battery. The sodium-ion battery was subjected to electrochemical performance testing on an electrochemical workstation under the following conditions: constant current charge-discharge, constant temperature of 25°C, and charge-discharge voltage range of 0–2.8V. The test results are shown in Table 2. The charge-discharge curve of the battery assembled from the hard carbon material prepared in Example 1 at a current density of 0.1C is shown in Table 2. Figure 1 .
[0087] Table 2
[0088]
[0089] As shown in Table 2, Examples 1-6, using the method of this disclosure, produced resin-based hard carbon materials with a three-dimensional network structure. When used in sodium-ion batteries, these materials exhibited a reversible capacity of over 320 mAh / g and a high initial discharge specific capacity. Comparative Examples 1-4, however, did not employ the method of this disclosure, resulting in materials with poor electrochemical performance. Specifically, Comparative Example 1 underwent curing in a tube furnace under static conditions, leading to the inability to release gases generated within the material, incomplete conversion of the C-COPNA resin, and uneven distribution, resulting in a low reversible capacity in the battery. Comparative Example 2 did not undergo curing, resulting in incomplete cross-linking of the material. The hard carbon material obtained after carbonization did not form a distinct short-range ordered and long-range disordered graphite sheet structure, leading to low initial discharge specific capacity, reversible capacity, and coulombic efficiency. Comparative Example 3 did not involve pulverization before curing, affecting the subsequent curing and oxidation reactions, resulting in low reversible capacity and coulombic efficiency. Comparative Example 4 did not use low-temperature pre-crosslinking, but instead carried out pre-crosslinking at 300°C. At this temperature, the asphalt reacted violently with the crosslinking agent, rapidly expanding and foaming, making it impossible to obtain a uniform and high-content B-COPNA resin, resulting in a low initial discharge specific capacity and reversible capacity of the battery.
[0090] Depend on Figure 1 It can be seen that the sodium-ion battery assembled in Example 1 has a high charge and discharge capacity, indicating that the hard carbon material prepared in Example 1 has excellent electrochemical performance.
[0091] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0092] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
Claims
1. A method for preparing resin-based hard carbon materials, characterized in that, The method includes: (1) Pre-crosslinking is performed by contacting asphalt with a crosslinking agent, wherein the pre-crosslinking temperature is below 300°C, to obtain a first resin product; (2) The first resin product is crushed to make the resulting resin particles move and then solidified to obtain the second resin product. (3) Oxidize and carbonize the second resin product.
2. The method according to claim 1, characterized in that, In step (1), the ash content in the asphalt is less than 0.01% by mass and the metal content is less than 10 μg / g.
3. The method according to claim 1, characterized in that, The asphalt includes one or more of natural asphalt, coal-based asphalt, and petroleum-based asphalt. The coal-based asphalt includes coal tar pitch and / or direct coal liquefaction pitch. The petroleum-based asphalt includes vacuum residue pitch and / or heavy aromatic hydrocarbon pitch. The crosslinking agent comprises an oxygen-containing organic compound having one or more of hydroxyl, carboxyl, and aldehyde groups; preferably, the oxygen-containing organic compound contains a benzene ring; more preferably, the oxygen-containing organic compound comprises a phenolic compound having 6 to 20 carbon atoms and 1 to 3 phenolic hydroxyl groups.
4. The method according to claim 1, characterized in that, In step (1), the weight ratio of the asphalt to the crosslinking agent is (0.5-4):1, preferably (1-2):1; The pre-crosslinking temperature is 150–250°C, preferably 200–250°C; the heating rate is 1–10°C / min; and the holding time is 10–60 min.
5. The method according to claim 1, characterized in that, In step (2), the method of achieving the motion state includes placing the resin particles in a rotary heating furnace for rotation, wherein the rotation speed of the rotary heating furnace is 1 to 30 r / min; The curing temperature is 250–450℃, preferably 320–450℃; the heating rate is 1–10℃ / min; and the holding time is 1–5h.
6. The method according to claim 1, characterized in that, In step (2), the pulverization conditions include: pulverizing the first resin product using a pulverizer until the particle size D10 is <1μm, D50 is <5μm, and D90 is <10μm, to obtain resin particles, and then curing the resin particles.
7. The method according to claim 1, characterized in that, In step (3), the oxidation conditions include: in an air or oxygen atmosphere, the second resin product is heated to 200-400°C, preferably 320-400°C, at a heating rate of 1-10°C / min for oxidation, and the oxidation isothermal time is 2-6 hours.
8. The method according to claim 1, characterized in that, In step (3), the carbonization conditions include: in an inert gas atmosphere, the oxidized product is heated to 1100-1600℃, preferably 1300-1600℃, at a heating rate of 1-10℃ / min for carbonization, and the carbonization isothermal time is 2-8h; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.
9. A resin-based hard carbon material prepared by the method according to any one of claims 1 to 8.
10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode includes the resin-based hard carbon material as described in claim 9.
Citation Information
Patent Citations
Hard carbon / graphite composite negative electrode material and lithium ion battery as well as preparation method and application thereof
CN111244407A
Preparation method of COPNA resin-based carbon sodium ion battery negative electrode material
CN117466279A